The Berenstain Bear Scouts and the white-water mystery - Berenstain, Stan, 1923-2005.; Berenstain, Jan, 1923-2012.; Berenstain, Michael (New York : Scholastic Inc., 1999)
The Bear Scouts are determined to solve the mystery of how Too-Tall and his gang beat them in a race through the river's rapids.
"Cartwheel books."
"Ages 6-10"--cover p. [4].
Keywords: Bears -- Fiction; Scouting (Reconnaissance) -- Fiction; Scouting (Youth activity) -- Fiction; Scouts (Reconnaissance) -- Fiction; Scouts (Youth organization members) -- Fiction; White-water canoeing -- Fiction; Mystery fiction